Geneva, from Car-euphoria to Opening of the Borders: Trajectory and Coordination of Transport and Urban Planning Policy - Maksim, Hanja (European Journal of Transport and Infrastructure Research, 2012)
Over the last two decades, urban planning has been reapplied in several European countries: common tendencies that underline the reform of planning procedures are the generalization of sustainable development and the reorganization of local government. Bringing an additional degree of complexity to planning procedures, the implementation of sustainable development appears to be strongly dependent of an effective and efficient inter-sectorial coordination between urban and transport policies. However, beyond these common evolutions, large differences appear in practice, depending on political cultures, planning traditions, and local contexts. This recent need for coordination, commonly considered a condition for success within urban sustainable development strategies, leads us to question the role of urban planning procedures and its evolution by analysing a specific case study, the cross-border agglomeration of Geneva, Switzerland, and reconstituting its “trajectory” during the last forty decades. The policy paths of the Genevan urban area have been described by considering the evolution of successive master plans, the implemented technical solutions and projects and the different means used in favour of an inter-sectorial coordination. For this analysis, factors of change or inertia in terms of have been identified by focusing on three main variables: ideas, institutions and interests. The case of Geneva illustrates how planning procedures take an integral part in the policymaking process, with these procedures elaborated simultaneously with policies. Torn between the renewal of public policy goals and the outcome of new territories, the reform of urban planning presents several contradictions. Conversely, sustainable development particularly fails to be addressed as a true political issue, limited to a definition of norms or legitimizing local policies.